2015
DOI: 10.1002/lt.24086
|View full text |Cite
|
Sign up to set email alerts
|

Impact of elderly donors for liver transplantation: A single‐center experience

Abstract: Elderly donor grafts for liver transplantation (LT) are recognized to be marginal grafts. The present study investigated the impact of using elderly donors for LT. Between June 1990 and August 2012, 1631 patients received LT at Kyoto University Hospital. Out of 1631 patients, 1597 patients received living donor liver transplantation (LDLT), whereas the other 34 patients underwent deceased donor liver transplantation (DDLT). Seventy-five grafts that were used came from individuals who were 60 years old. We retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…We also reported that the overall survival rates of recipients with HCV were significantly lower after receiving grafts from elderly, ≥ 60 years old, compared with younger donors [9]. Berenguer et al reported that outcomes among HCV-positive recipients were worsened by more advanced donor age and more powerful immunosuppression [22].…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…We also reported that the overall survival rates of recipients with HCV were significantly lower after receiving grafts from elderly, ≥ 60 years old, compared with younger donors [9]. Berenguer et al reported that outcomes among HCV-positive recipients were worsened by more advanced donor age and more powerful immunosuppression [22].…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, overall survival rates did not differ in all subgroups of HCV-positive recipients who received grafts from younger and non-younger donors. For this reason, we defined donors aged < 40 years as being younger in this study, while our previous report compared overall survivals of recipients between elderly (≥ 60 years old) and non-elderly donors [9]. In fact, moreover, overall survival rates of adult-to-adult LDLT in and after April 2006 did not differ significantly between the elderly group and the younger group [9].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations